Constitutive activity of GPR26 regulated by ubiquitin‐dependent degradation and its antitumor role. (1st March 2021) - Liu, Fang; Yang, Wei; Hu, Minghui; Zhang, Yong; Sun, Beicheng; Yang, Hao; Brosius, Juergen; Deng, Cheng
Abstract : G protein‐coupled receptors (GPCRs) play important roles in many physiological functions and numerous diseases. In addition to the classic ligand‐stimulated receptor activity, an increasing number of studies have established that many GPCRs function constitutively in a receptor dose‐dependent manner. Previous observations showed that following gene transfection, little or no protein was detectable for certain GPCRs (designated apparent state A), such as GPR26, GPR39, GPR78, GPR133, GPR139, BRS3, and LGR5, which showed strong constitutive activities. When we lysed cells in the immediate presence of western blot loading buffer, a significant increase of protein levels was detected (actual state B), which was much closer to the true expression levels under physiological conditions. GPR26 was chosen for further functional experiments as the actual state B. We identified an important ubiquitination site, K286, as well as the ubiquitin ligase E3 homologous to the E6‐associated protein carboxyl terminus domain containing 3 interacting with GPR26. The pronounced differences in the protein expression and constitutive activity of GPR26 were a consequence of the ubiquitin‐mediated rapid degradation mechanism. Furthermore, we identified in vitro and in vivo antitumor activity associated with high expression levels and constitutive activity of GPR26 in liver cancer cells. Hence, GPR26 could act as an antitumor gene for hepatocellular carcinoma. This study also represents the actual state B of a batch of GPCRs that actually play potentially important roles in physiological functions by their constitutive activity, which is controlled by rapid ubiquitin‐dependent degradation. Abstract : The outline of ubiquitin degradation regulated expression and anti‐tumor activity of GPR26 in liver cancer. We identified an important ubiquitination site‐K286 and a ubiquitin ligase E3‐homologous to the E6‐associated protein carboxyl terminus domain containing 3 (HECTD3) interacting with GPR26. The pronounced differences in protein expression and constitutive activity of GPR26 were a consequence of ubiquitin‐mediated degradation. Furthermore, GPR26 exhibits evident anti‐tumor activity by promoting liver cancer cell apoptosis and inhibiting its proliferation, migration, invasion and stemness via Gs constitutive activity.